Combination of Cell-Penetrating Peptides with Nanoparticles for Therapeutic Application: A Review - Sara Silva; António J. Almeida; Nuno Vale (Biomolecules, 2019)
Cell-penetrating peptides (CPPs), also known as protein translocation domains, membrane translocating sequences or Trojan peptides, are small molecules of 6 to 30 amino acid residues capable of penetrating biological barriers and cellular membranes. Furthermore, CPP have become an alternative strategy to overcome some of the current drug limitations and combat resistant strains since CPPs are capable of delivering different therapeutic molecules against a wide range of diseases. In this review, we address the recent conjugation of CPPs with nanoparticles, which constitutes a new class of delivery vectors with high pharmaceutical potential in a variety of diseases.